THE CORRELATION BETWEEN READING COMPREHENSION AND VOCABULARY MASTERY (A STUDY CONDUCTED AT SMA NEGERI 1 KOTAMOBAGU) - Mokoginta, Tria Ningsi; Liando, Nihta V. F.; Wungow, Trully (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
This study investigates the correlation between students' reading comprehension and their vocabulary mastery in the first grade of SMA Negeri 1 Kotamobagu. Data were collected from 32 first grade students from XK class. The test item of reading comprehension and vocabulary mastery were given to the students to measure their level of reading comprehension and vocabulary mastery. The results were compared to find out the correlation between those variables. The researcher analyzed the data by using the formula of Pearson Product Moment. The significant value was 0.000 ≤ 0.005, indicating that there was a relationship between reading comprehension and vocabulary mastery among the students. According to the data, 0.671 is the value of the correlation coefficient it ranges from 0.40-0.70 it is clear that there is a positive degree of relevance relationship. The correlation test gave a score of 0.671, indicating a moderate level of correlation. The researcher discovered a positive relationship between students' reading comprehension and vocabulary mastery in first grades of SMA Negeri 1 Kotamobagu.